The stress level of future teachers depending on the direction of professional subject training - N. Yu. Galoy (Вестник университета, 2024)
The article describes the influence of university educational environment on the formation of resistance to stress in future teachers. A theoretical analysis of the phenomenon of psychological stress as a state of mental tension manifested in emotional, behavioural and somatic sensations is presented. The results of testing 529 students, who were examined in April 2022, using the PSN-25 methodology were analysed. The features of the stress level of future teachers are formulated and statistically substantiated, depending on the direction of professional subject training (foreign language, music, physical education), course of study, gender. It was found that more than half of all respondents do not experience excessive mental stress. The number of students with a low level of stress increases from the first year to the third one, regardless of the direction of professional subject training. Among future foreign language teachers, a relatively higher level of mental stress prevails. This trend is statistically significant for the first-year students of the sample. Future of physical education and music teachers are more normalised in terms of mental stress which may be due to the peculiarities of educational environment of these faculties and due to the nature of educational and professional activities. Significant gender differences in the prevalence of higher stress levels in young ladies compared to young men were revealed in a sample of these two directions of training.